Sustainability in healthcare waste: Integrative review (Research, Society and Development, 2024)
This study is a literature review with a qualitative approach and aimed to identify the practices developed by nurses in Health Service Waste Management in the light of sustainability. The management of this waste is defined as all the actions carried out to manage it, and the nurse manager is responsible for its proper functioning, who guides his team. For data collection, the following databases were used: Scielo, LILACS, BDENF, Coleciona SUS and Medline, reaching 12 articles. The results allowed the formation of the following thematic categories: knowledge about disposal of Health Service Waste; proper disposal and sustainability suggestions; and ongoing education on Health Service Waste. It is concluded that it is necessary for health professionals to be trained to dispose of Health Service Waste in all environments that provide health care, according to the needs of the units.